2021
DOI: 10.25307/jssr.902511
|View full text |Cite
|
Sign up to set email alerts
|

Hemşirelerin Fiziksel Aktivite Düzeyleri ile Yaşam Kalitesi ve Tükenmişlik Düzeyleri Arasındaki İlişkinin İncelenmesi

Abstract: Bu çalışmanın amacı, hemşirelerin fiziksel aktivite düzeyleri ile yaşam kalitesi ve tükenmişlik düzeyleri arasındaki ilişkinin incelenmesidir. Çalışmaya, Hitit Üniversitesi Erol Olçok Eğitim ve Araştırma Hastanesi’nde görev yapan 212 hemşire katılmış ve katılımcıların tamamına Fiziksel Aktivite Ölçeği, SF-36 Yaşam Kalitesi Ölçeği ve Maslach Tükenmişlik Envanteri uygulanmıştır. Shapiro-Wilk testi sonuçlarına göre, verilerin normal dağılıma uygun olmadığı görüldüğünden (p<0,05), ikili gruplar karşılaştırm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 22 publications
1
3
0
4
Order By: Relevance
“…It was determined that the most frightening situation for the participants during the pandemic process was generally infecting their family members, and therefore they thought of resigning during the pandemic process. These data are compatible with other study results [19,20].…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…It was determined that the most frightening situation for the participants during the pandemic process was generally infecting their family members, and therefore they thought of resigning during the pandemic process. These data are compatible with other study results [19,20].…”
Section: Discussionsupporting
confidence: 94%
“…In a study examining the variables of quality of life, it was reported that professional quality of life was affected by choosing the profession voluntarily and choosing to work in the unit [43]. In another study, it was reported that those who voluntarily chose the profession had higher quality of life scores [19]. In another study, it was observed that mental symptoms were observed much more frequently in healthcare workers with a chronic disease or those over 65 years of age, or those who shared the same house with family members with chronic diseases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Koronavirüs enfeksiyonu 30 Ocak 2020 tarihinde Dünya Sağlık Örgütü tarafından Uluslararası Endişe Duyulan Halk Sağlığı Acil Durumu ilan edildi. (1) Koronavirüs salgını süresince enfekte olduğu belirlenmiş veya şüphesi olan pek çok hastanın acil tedavi ihtiyacında artış oldu ve hastanelerde tedavi gören hasta sayısı yükseldi.…”
Section: Introductionunclassified